Role of Fe-oxides for predicting phosphorus sorption in calcareous soils - Memon, Mehruinsa (Karlsruher mineralogische und geochemische Hefte : Schriftenreihe des Instituts für Mineralogie und Geochemie, 2008)
Agronomic efficiency and management of environmental P inputs can be improved by understanding soil-phosphorus interaction. Iron oxides and other clay minerals, P forms, and P sorption in young alluvial and weathered residual soils were determined. Phosphorus retention related to crystallinity and phase distribution of iron oxides. CBD and oxalate extractable iron and aluminum and smectite and kaolinite explained 90% variation while soil CaCO3 role was only insignificant in explaining P sorption.